T Cell Lymphoma in An Akkaraman Sheep - Ceribasi, Songul; Ozkaraca, Mustafa; Ceribasi, Ali Osman; Ozer, Harun (Kafkas Univ, Veteriner Fakultesi Dergisi, 2013)
Lympocytic T cell lymphoma was detected in liver and kidneys of a 3 year old Akkaraman sheep which was submitted to the pathology department for diagnosis. Macroscopically, nodular formations with white colour and about 1 cm size were observed in the cortex of both kidneys. The irregular nodules were observed in the liver, similar to the lesions in the kidneys. Microscopically, the nodular lesions in the liver and kidneys were consisted of uniform lymphocytic accumulations. These lymphocytes were similar to the mature lymphocytes although they were bigger and had less chromatin. Immunohistochemically, tumor cells had positivity with CD3, but negativity with CD20 and CD79a. Thus, the tumor was described as type of lymphocytic T cell lymphoma.
Bir akkaraman koyunda t hücreli lenfoma
Keywords: Akkaraman sheep; Immunohistochemistry; Lymphoma